Determination of technological parameters of Zn-Al layered double hydroxides, as a matrix for functional anions intercalation, under different synthesis conditions - Kovalenko, Vadym; Borysenko, Anastasiia; Kotok, Valerii; Nafeev, Rovil; Verbitskiy, Volodymyr; Melnyk, Olena (Eastern-European Journal of Enterprise Technologies, 2022)
Layered double hydroxides, especially Zn-Al, are valuable bases for intercalating various functional anions: dyes, drugs, food additives, etc. For purposeful development and optimization of the synthesis technology of functional materials based on Zn-Al layered double hydroxides, the technological parameters of Zn-Al nitrate layered double hydroxide samples (Zn:Al=4:1) synthesized at solution flow rates of 0.8 and 1.6 l/h, pH=7, 8, 9, 10 and t=10, 20, 30, 40, 50 and 60 °C were determined. The yield values of the samples were determined by the gravimetric method. The sedimentation rate was studied by measuring the normalized thickness of the precipitate layer (relative to the initial layer thickness) during 30 minutes of settling. It was found that with an increase in the synthesis pH, the yield increased from 74.68 % to 83.54 %. Increasing the flow rate of the solutions led to a decrease in yield. On the yield-synthesis temperature dependence, two sections of 10–20 °C and 30–60 °C were identified, within which an increase in temperature led to a decrease in yield. It is shown that with increasing synthesis pH, as well as the solution flow rate, the sedimentation rate increased significantly. At pH=10, almost complete sedimentation of the sample occurred within the first 5 minutes. The obtained data indicate that the pH of the zero charges of the Zn-Al-NO3 layered double hydroxide particles was close to 10. It was found that increasing the temperature reduced the sedimentation rate. An abnormally low sedimentation rate at a synthesis temperature of 30 °C and an abnormally high sedimentation rate at 50 °C were detected. The obtained data confirm the previously stated hypothesis regarding the change of the mechanism or kinetics of the formation of layered double hydroxides at temperatures of 30 °C and 50 °C